Multidisciplinary Collaborative Reliability Analysis of the Gear Reducer based on Inverse Reliability Strategy - Wang Liangliang; Peng Jinshuan; Shao Yiming (Jixie chuandong)
To overcome the high computational cost of reliability analysis,a reliability analysis method which combines the multidisciplinary genetic algorithm collaborative optimization（ GA- CO） based on the inverse reliability strategy（ IRS） is proposed（ IRS- GA- CO）. The genetic algorithms- based collaborative optimization（ GA- CO） is one of the improved forms of CO that overcomes the difficulty of convergence given the existing of highly nonlinear consistency constraints. The IRS- GA- CO,which not only lifted the coupling between all disciplines to improve the search most probable point,the burden of system- level optimizer also can be significantly reduced. Examples of speed reducer prove the efficiency and precision of the proposed method.What is more,this advantage in the design of large- scale complex engineering systems will be better reflected.